AN ANALYSIS OF STUDENT LEARNING EXPERIENCE TOWARD FULLY INSTRUCTION OF WEB - BASED LEARNING DURING THE PANDEMIC OF COVID – 19 - maliqul hafis; Mega - Herawati; Mifta - Rahman (XXXX-XXXX, 2021)
This research aimed to figure out student learning experience toward fully instruction of web-based learning during the pandemic of covid-19 in IKIP PGRI Pontianak. Descriptive qualitative method was implemented in this research. The total sample were 30 students from the second semester of English Education Program at IKIP PGRI Pontianak in the academic year of 2019/2020.  It was determined by cluster sampling which took A Morning Class. This research used open-ended questions designed by Vai and Sosulski (2011) which consisted of four elements learning experience namely learner, mentor, knowledge and environment as the indicator of this research. There were 10 questions in the questionnaire. The data findings analyzed by using transcription. Triangulation was implemented in this research to determine the accuracy or the credibility of the data findings. The research findings indicated that the implementation of web-based learning was convenient for the students to keep continuing the learning activities during the pandemic of covid-19. However, the student still preferred conventional (face-to-face) learning because the intensity of teaching learning process made lecturers’ explanation easier for them to comprehend the material. Though the lecturers’ instructions and feedback during learning via the web was satisfied and supported the students but it did not help them much because of some reasons such as bad internet connection. Most of students live in a village that has bad internet connection. It made some of the students had to go to downtown in order to get good internet connection so they would not missed the class but sometimes the lecturers did not start the class on the schedule. So, they felt difficult to follow the class. Besides, the students also felt difficult to ask or discuss regarding the materials they did not understand even though the lecturers let them ask whenever they were confused but it was hard to understand by texting or chatting. Without understanding the materials, they should finish all assignments by the deadline given. Due to this case, during web-based learning the students wanted the content design for the material display in a video format thus they can download it after the signal is available. Perhaps, it can help them understand the material and do not worry about the signal error. In conclusion, the students actually could not study well through web based learning. They wanted to study as usual in a class by convenient or face to face learning. Keywords: Student learning experience, web-based learning, pandemic of covid-19.